2001
DOI: 10.1016/s0008-6363(00)00243-1
|View full text |Cite
|
Sign up to set email alerts
|

Time course of arteriogenesis following femoral artery occlusion in the rabbit

Abstract: We conclude that the chemokine MCP-1 markedly accelerated collateral artery growth but did not alter its final extent above that reached spontaneously as a function of time. We show thus for the first time that a narrow time window exists for the responsiveness to the arteriogenic actions of MCP-1, a feature that MCP-1 may share with other growth factors. We show furthermore that the spontaneous adaptation by arteriogenesis stops when only about 50% of the vasodilatory reserve of the arterial bed before occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
169
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(177 citation statements)
references
References 22 publications
4
169
2
2
Order By: Relevance
“…This morphology, identified in our experiments exclusively after MCP-1 treatment, is typical for arteries induced by arteriogenesis. 22,24 The concomitant increase in the number and diameter of induced collateral arteries are in good agreement with the pronounced increase in peripheral conductance between control-and MCP1_genomic-treated pigs. In addition, other enlarged or induced blood vessels not visualized by angiography may additionally contribute to the peripheral conductance.…”
Section: Mcp-1 Gene Transfer-mediated Arteriogenesis a Muhs Et Alsupporting
confidence: 78%
See 3 more Smart Citations
“…This morphology, identified in our experiments exclusively after MCP-1 treatment, is typical for arteries induced by arteriogenesis. 22,24 The concomitant increase in the number and diameter of induced collateral arteries are in good agreement with the pronounced increase in peripheral conductance between control-and MCP1_genomic-treated pigs. In addition, other enlarged or induced blood vessels not visualized by angiography may additionally contribute to the peripheral conductance.…”
Section: Mcp-1 Gene Transfer-mediated Arteriogenesis a Muhs Et Alsupporting
confidence: 78%
“…This is comparable to improvements of conductance mediated by continuous infusion of MCP-1 protein in rabbit and pig. 22,23 The present study showed for the first time that a nonviral gene therapeutic approach was equipotent to a protein perfusion therapy. Transfection of 2 mg MCP-1_genomic led to significant improvements of conductance and to an increase in peripheral blood pressure.…”
Section: Mcp-1 Gene Transfer-mediated Arteriogenesis a Muhs Et Almentioning
confidence: 61%
See 2 more Smart Citations
“…8 Experimental therapy with growth factors can improve on that by not more than several percentage points. 9 Increased FSS is thought to be responsible for triggering arteriogenesis, 10,11 because the sudden decrease in peripheral pressure after an arterial occlusion increases the velocity of flow in pre-existent collateral arterioles that interconnect the prestenotic high-pressure bed with the poststenotic lowpressure bed.…”
Section: Discussionmentioning
confidence: 99%